A Case Study on Ambalamugal Medical Aid Society Initiative by BPCL-Kochi Refinery - Krishnan, Chitra (Prabandhan: Indian Journal of Management, 2012)
CSR is a concept whereby large organizations consider the interests of society by taking responsibility for the impact of their activities on customers, suppliers, employees, shareholders, communities and other stakeholders, as well as the environment. As the world continues to analyze energy availability and the long-term effects of climate change, businesses too are turning their attention to an area of opportunity - reduction of carbon emissions, energy conservation and supply chain sustainability. CSR holds organizations to a higher moral and ethical standard, considering the overall interests of society in the operations of its day-to-day businesses. An approach for CSR that is becoming more widely accepted is community-based development approach. In this approach, corporates work with local communities to better themselves. For example, the Shell Foundation’s involvement in the Flower Valley, South Africa. A more common approach of CSR is Philanthropy. This includes monetary donations and aid given to local organizations and impoverished communities in developing countries. Some organizations do not like this approach, as it does not help build on the skills of the local people, whereas, community-based development generally leads to a more sustainable development. Another approach to CSR is to incorporate the CSR strategy directly into the business strategy of an organization. For instance, procurement of Fair Trade tea and coffee has been adopted by various businesses, including KPMG. Its CSR manager commented, "Fair-trade fits very strongly into our commitment to our communities".